Policies to sustain the nursing workforce: an international perspective. (13th January 2015) - Buchan, J.; Twigg, D.; Dussault, G.; Duffield, C.; Stone, P.W.
<x xml:space="preserve">Abstract</x> Aim Examine metrics and policies regarding nurse workforce across four countries. Background International comparisons inform health policy makers. Methods Data from the OECD were used to compare expenditure, workforce and health in: Australia, Portugal, the United Kingdom (UK) and the United States (US). Workforce policy context was explored. Results Public spending varied from less than 50% of gross domestic product in the US to over 80% in the UK. Australia had the highest life expectancy. Portugal has fewer nurses and more physicians. The Australian national health workforce planning agency has increased the scope for co‐ordinated policy intervention. Portugal risks losing nurses through migration. In the UK, the economic crisis resulted in frozen pay, reduced employment, and reduced student nurses. In the US, there has been limited scope to develop a significant national nursing workforce policy approach, with a continuation of State based regulation adding to the complexity of the policy landscape. The US is the most developed in the use of nurses in advanced practice roles. Ageing of the workforce is likely to drive projected shortages in all countries. Limitations There are differences as well as variation in the overall impact of the global financial crisis in these countries. Conclusion Future supply of nurses in all four countries is vulnerable. Implications for nursing and health policy Work force planning is absent or restricted in three of the countries. Scope for improved productivity through use of advanced nurse roles exists in all countries.